El Trabajo de Grupo dentro del Ambito de la Animación Comunitaria - Froufe Quintas, Sindo (Teoría de la Educación. Revista Interuniversitaria, 2009)
Community Animation within the limits of social interaction is one of the best strategies for achieving social transformation and change. The community as a point of reference for individual identity is composed of territory, identification of affective bonds, solidarity and communicative commitment with regards to values. The structure of the group and the funtions of the community animator should be combined through active participation in the creation of a collective conscience in the field of Social Work. Territorial analysis tries to improve the conditions which favour the phenomena of mutual help and reciprocity thereby favouring the social progress of a particular community.